Pengaruh Work Life Balance dan Job Satisfaction Terhadap Organizational Citizenship Behaviour Pada Biro Umum Kementerian “X” - Zahra Khumaira; Sholikhah Sholikhah; Christian Wiradendi Wolor (CV. ULIL ALBAB CORP, 2024)
This research aims to determine: 1) The effect of work life balance on organizational citizen behaviour (OCB). 2) The effect of job satisfaction on organizational citizen behaviour (OCB). 3) The effect of work life balance and job satisfaction on organizational citizen behaviour (OCB). This research was conducted at the General Bureau of Ministry “X” with a sample of 105 employees which was a saturated sample. This research method is a survey method using a questionnaire with a quantitative approach. The results of this study indicate that 1) Work life balance has a positive and significant effect on organizational citizen behavior (OCB), 2) Job satisfaction has a positive and significant effect on organizational citizen behavior (OCB), and 3) Work life balance and job satisfaction simultaneously affect organizational citizen behavior (OCB).